International Review Research in Developmental Disabilities - Hodapp, Robert M; Fidler, Deborah J (International Review of Research in Developmental Disabilities, 2021)
International Review of Research in Developmental Disabilities, Volume 60 highlights new advances in the field, with this new volume presenting interesting chapters written by an international board of authors, including updates on School-based Executive Function Interventions Reduce Caregiver Strain, Emergence of Fine Motor Skills in Down.